NATURALISTIC AND POSITIVISTIC DEBATES ON IMPLEMENTING THE CAPITAL PUNISHMENT - Thilakarathna, K.A.A.N. (My University, 2019)
Implementation of the death penalty is a contemporary issue in most parts of the universe. It lies at the heart of retributory justice and is still practiced by a significant part of the globe. While many countries have abolished the death penalty either de jure or de facto, there are still several arguments both for and against the implementation of the death penalty. Regarding these arguments it then becomes important to see whether there is any merit in the jurisprudential arguments specially from the natural law and positivistic schools of legal thought. The proponents of natural law who base their arguments on the connection of law and morality both argue for and against the death penalty and, proponents of the positivistic school are strongly adamant about the validity of the implementation of the death penalty. In the above back drop this paper examines the ideas put forward by Lon Fuller and John Finnis regarding the natural law thinking and, the ideas of H.L.A. Hart and Hans Kelson from the positivistic perspective.
Keywords: HLA Hart, Lon Fuller, John Finnis, Kelsen, Capital Punishment, Theories of Punishment